The Sociological Effects of Cashless Policy on Church Income in Surulere Archdeaconry, Diocese of Lagos Mainland (Anglican Communion) - Ogunbiyi, David Oluwabukunmi (Scriptura Indonesia, 2025)
This study explores the impact of Nigeria’s cashless policy on church income within Surulere Archdeaconry, Diocese of Lagos Mainland (Anglican Communion). Introduced by the Central Bank of Nigeria to modernize payment systems and reduce cash-related issues, the policy has compelled churches to adapt to digital financial platforms. However, the transition has presented significant challenges, including poor network infrastructure, limited awareness, digital illiteracy, and theological concerns among members. These barriers have led to a noticeable decline in tithes, offerings, and other forms of giving. Using a descriptive survey research design, the study engaged 150 respondents—comprising clergy, wardens, accountants, and auditors—from five major parishes in the Archdeaconry. Data were collected through structured questionnaires and oral interviews and analyzed using simple percentages. Findings revealed that 84% of participants experienced disruptions in giving due to failed electronic transactions, lack of awareness of e-payment systems, and unreliable network services. Despite these challenges, the majority acknowledged the convenience and security of digital giving platforms and supported their continued implementation. The study recommends that churches provide more electronic payment options such as POS terminals, mobile transfers, and USSD codes, while also raising awareness and offering training to members. Collaborative efforts with banks and government agencies to improve technological infrastructure and enforce fraud protections are also vital. In conclusion, while the cashless policy initially hindered church income, it presents long-term benefits if properly managed. Churches must adopt inclusive digital strategies to align with national financial reforms and ensure sustainable income flow.